Estudo químico em patógenos e vetores de doenças de citros: Xylella fastidiosa e Diaphorina citri - Andrade, Moacir dos Santos (Universidade Federal de São Carlos, 2011)
CHEMICAL STUDY OF PATHOGENS AND VECTORS DISEASE OF CITRUS: Xylella fastidiosa & Diaphorina citri. Historically the national citriculture suffered great changes because of phytosanitary problems, and nowadays among the main threats to citruculture are the Huanglongbing (HLB) or Greening and the Citrus Variegated Chlorosis (CVC). The bacteria Xylella fastidiosa is the etiologic agent of Citrus Variegated Chlorosis. The HBL is associated to a bacterium that belongs to the Candidatus Liberibacter genera and its dissemination is by grafting of infected material or by psyllids. This work describes the chemical study of bacteria Xylella fastidiosa and the olfatometric response of Diaphorina citri to Citrus species. The X. fastidiosa (9a5c) were cultivated in PW medium. In the chemical study of X. fastidiosa the identification techniques used were CG-EM, LC-MS e LC-SPENMR. These techniques allowed the identification of fatty acid derivatives and diketopiperazinic alkaloids. This is the first chemical study of X. fastidiosa that boarded the alkaloids production cyclo (Pro-Val), cyclo (Val-Phe), cyclo (Tyr-Tyr), cyclo (Phe-Tyr), cyclo (Pro-Phe), cyclo (Leu-Leu), cyclo (Leu-Ile), cyclo (Val-Leu), cyclo (Ala-Leu), cyclo (Ala-Pro) cyclo (Pro-Leu), cyclo (Pro-Tyr), cyclo (Tyr-Pro), cyclo (Tyr-Val), cyclo (Pro-Ile), cyclo (Phe- Ile), cyclo (Arg-Val), cyclo (Leu-Phe), cyclo (Gly-Phe). Volatile compounds produced by X. fastidiosa extracted by SPME allowed the identification of methyl ketones and alcohols. The behavior study of D. citri to Citrus species essential oils, using olfatometric assays showed higher attractiveness to Citrus reticulata Blanco, Citrus paradisi Macfad., Citrus medica L. and the standard Murraya paniculata. However, lower attractiveness of D. citri was observed to hybrid species tangor Murcott, citrumelo Swingle e citrange Trover, that showed a high percentual of sesquiterpene compounds in the chemical composition. As complementary subsidy for understanding the interactions between D. citri-host the Principal Components Analysis (PCA) and Hierarchical Clusters Analysis (HCA) were carried out, these analyses demonstrated a group between tangor Murcott e citrumelo Swingle that indicate chemical similarity.
Keywords: Química orgânica; Clorose Variegados Citros; Cromatografia líquida de alta eficiência; Cromatografia gasosa; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA